Modelling and control of the modular multilevel matrix converter and its application to wind energy conversion systems - Diaz, Matias; Cardenas, Roberto; Espinoza, Mauricio; Mora, Andreas; Wheeler, Patrick (2016)
In the last past years, some countries are enforcing stringent grid codes to regulate the connection of Wind Energy Conversion Systems (WECSs) to the electrical network, mainly because of the high penetration of electric power from this renewable source. Additionally, the trend of wind turbines has shown an ongoing power rating growth, reaching sizes up to 10 MW. Multilevel converters appear then as a promising solution for large WECSs, due to its high reliability, controllability and the capability to reach high power ratings. In this scenario, this paper presents a control strategy for the application of the Modular Multilevel Matrix Converter in Multimegawatts Wind Turbines. Extensive computer simulations and a downscaled laboratory prototype, with twenty-seven power cells, are presented to validate the effectiveness of the proposed control system.